The long goodbye - Davis, Patti (New York, NY Alfred A. Knopf, 2004)
The daughter of Ronald Reagan describes losing her father to the ravages of Alzheimer's, linking memories of her life to a study of Reagan the man, the actor, and the politician, and the toll of the disease on her father and his family
D,10/05, Raymond L Parent & Loretta "Madore" Parent
Keywords: Reagan, Ronald -- Biography; Presidents -- United States -- Family relationships -- Biography; Davis, Patti -- Biography; Raegan, Ronald -- Health -- Biography; Alzheimer's disease -- Patients -- United States -- Biography